Mg vacancy and dislocation strains as strong phonon scatterers in Mg2Si1−xSbx thermoelectric materials. (April 2017) - Xin, Jiazhan; Wu, Haijun; Liu, Xiaohua; Zhu, Tiejun; Yu, Guanting; Zhao, Xinbing
Abstract: Mg2 Si based solid solutions have unique advantages in the direct thermal to electrical energy conversion due to environmentally friendly and abundant constituent elements, and high thermoelectric performance. Further enhancing figure of merit zT of this materials system lies in the reduction of the relatively high lattice thermal conductivity. Alloying by high content of aliovalent Sb (>10%) in Mg2 Si can greatly suppress the lattice thermal conductivity, lower than conventional Mg2 (Si, Sn) solid solutions, due to the enhanced phonon scattering from Mg vacancy and concomitant strains. In this work, detailed microstructure observation for Sb alloyed Mg2 Si reveal the existence of dense dislocations, around which the strip-like defects are viewed with isotropic strain. By introducing dislocations and vacancies as the additional phonon scattering sources, the model calculation can well match the experimental lattice thermal conductivity. The present work offers a comprehensive understanding of the role of vacancies and concomitant strains in reducing thermal conductivity, and may open a new venue for zT enhancement. Graphical abstract: The high contents of aliovalent Sb alloying in Mg2 Si not only result in Mg vacancy, but also induce dense dislocations with intensive strain accumulation, which act as extra phonon scatterers and contribute to the significantly reduced lattice thermal conductivity in the Sb alloyed Mg2 Si, compared to the Sn alloyed Mg2 Si with the same amount of Si sites substituted. Highlights: Sb alloying in Mg2 Si can suppress the lattice thermal conductivity, lower than conventional Mg2 (Si, Sn) solid solutions. Detailed microstructure observation for Sb alloyed Mg2 Si reveal the existence of dense dislocations. By introducing phonon scattering from dislocations, the model calculation can well match the experimental data. This work offers a comprehensive understanding of the role of vacancies and dislocations in reducing thermal conductivity.